1964
DOI: 10.1172/jci104925
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoglycemic Action of Ketones. II. Evidence for a Stimulatory Feedback of Ketones on the Pancreatic Beta Cells *

Abstract: The effects of alterations in carbohydrate metabolism induced by starvation and insulin deprivation on hepatic ketone production and peripheral ketone utilization have been the subject of intensive investigation (1-12). Only scant attention, however, has been paid to the effects that hyperketonemia, in turn, might have on carbohydrate and fat metabolism. The conflicting results from such studies (13-17) have been reviewed recently (18). Studies in this laboratory, designed to define the effects of induced hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
2

Year Published

1969
1969
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 225 publications
(75 citation statements)
references
References 33 publications
4
69
2
Order By: Relevance
“…This finding is consistent with other reports of decreased plasma glucose concentration associated with elevated BHBA in pregnant sheep Harmeyer 2003, 2004), dogs (Felts et al, 1964;Madison et al, 1964), and pigs (Müller et al, 1984). However, our findings are in contrast to other reports that described a hyperglycemia in rabbits (Mirsky and Broh-Kahn, 1937) induced by ketone bodies infusion.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding is consistent with other reports of decreased plasma glucose concentration associated with elevated BHBA in pregnant sheep Harmeyer 2003, 2004), dogs (Felts et al, 1964;Madison et al, 1964), and pigs (Müller et al, 1984). However, our findings are in contrast to other reports that described a hyperglycemia in rabbits (Mirsky and Broh-Kahn, 1937) induced by ketone bodies infusion.…”
Section: Discussionsupporting
confidence: 93%
“…Infusion of BHBA increases insulin secretion in pigs (Müller et al, 1984). Madison et al (1964) suggested that pancreatic beta cells respond to the high plasma BHBA concentration with increased insulin secretion in dogs. It appears that insulin suppresses the glucose production throughout an inhibitory effect on the regulatory enzymes of gluconeogenesis (Brockman and Larrveld, 1986;Hayirli, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 We observed that giving BHB-ketotic mice glucose not only increased the animals' blood glucose levels (Group #5), it elevated their HST (Group # 4 and #5) as compared to ketotic animals who did not receive glucose (Group #3). Our data, therefore, are consistent with the idea that increased substrate availability enhances hypoxic tolerance.…”
Section: Physiological Considerationsmentioning
confidence: 71%
“…One explanation for the proposed inhibition of glucose metabolism may be that GG has recently been shown to inhibit the activity of phosphofructokinase by decreasing the level of fructose 2,6-biphosphate in intact cells. 23 This inhibition would then suppress glucose utilization but not adversely effect BHB utilization since BHB does not utilize the glycolytic pathway. This contrasts with earlier studies of Lefebvre and Luyckx 24 who reported that GG had no direct effect on the peripheral glucose utilization.…”
Section: Physiological Considerationsmentioning
confidence: 99%